Female Land Rights and Rural Household Incomes in Brazil, Paraguay and Peru - Carmen Diana Deere; Rosa Luz Durán; Merrilee Mardon; Tom Masterson (University of Massachusetts, Department of Economics, 2004)
This paper explores the determinants of female land rights and their impact on household income levels among owner-operated farms in Brazil, Paraguay and Peru. Previous studies in Latin America suggest that the gender of the household head is not a significant predictor of household income, not unsurprising given the ambiguities with which self-declared headship is associated. We hypothesize that female land rights, by increasing women's options, are a positive determinant of household income, but given the disadvantages that they face as farmers, that their land rights will more likely impact upon off-farm rather than farm income. Regression analysis indicates that female land rights are positively related to off-farm income in Peru and Paraguay, but significantly so only in the case of dual-headed households in Peru where the bargaining power thesis is operative. They are negatively associated with farm income in both countries and with farm revenue in Brazil.
Keywords: 330; Gender; Land Rights; Household Income; Female-headed Households; Intrahousehold Bargaining Power; Latin America